Estar ahí, al cuidado de un paciente con demencia (2007)
ABSTRACT: Due to their organic losses demented patients evolve towards total invalidity. If they do not find caring people absolute destitution awaits them. Objective: To understand caregiver reasons for “being there” to a patient with dementia and what are his actions to remain giving care. Methodology: This grounded study was carried in Medellin from January 2002 to June 2004. Twenty-two people with a minimum three years caring of demented people were interviewed. These persons were contacted by the Universidad de Antioquia Neurosciences Caring persons group and by the Instituto de los Seguros Sociales senior citizens program. Manual analysis was performed. Results: “Being there” is a decision taken by the caregivers because they are sons or relatives of a demented person. This decision is motivated by four cultural factors: social and economic function in the group, tradition, reciprocity and religion. The feeling of fatigue of the caregivers was stressed and how they need information, learning from experience, reflection, support and participation in other activities. Conclusion: The person who gives care to a demented patient recognizes that “one alone cannot”. Accordingly, it is urgent to create ambiances and places which support health and welfare of these caregivers.